Efeito imunomodulador do 2-metoxi-4-(7-metoxi-1,2,3,4-tetrahidroisoquinolin-1-il)fenol (mhtp) em um modelo de lesão pulmonar aguda - Xavier, Bianka Márcia do Nascimento (2018)
Acute lung injury is a critical illness syndrome consisting of acute respiratory failure with cellular infiltrate and is characterized by alveolar capillary barrier injury, neutrophil accumulation and induction of proinflammatory cytokines, followed by pulmonary fibrosis. Due to the complexity of the physiological and immunological events involving acute lung injury, there is still no fully established pharmacotherapy. MHTP (2-methoxy-4-(7-methoxy-1,2,3,4-tetrahydroisoquinolin-1-yl)phenol) is an unprecedented synthesized alkaloid that has chemical similarity to the cryptostolins and alkaloids CKD712 ((S)-1-(a-naphthylmethyl)-6,7- dihydroxy-1,2,3,4-tetrahydroisoquinoline) and THI52 (1-naphthylethyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline). The purpose of this study was to investigate the pharmacological potential of MHTP in the treatment of experimental acute lung injury in two moments: 72 hours (acute phase) and 10 days (chronic phase). In order to perform this, the model of acute lung injury induced by LPS in male BALB / c mice was used. Three treatments were performed by nasal instillation with MHTP, the first one occurred one hour after challenge with LPS, the second with 24 hours and the third with 48 hours. To select the dose of the substance, a pilot experiment was carried out at doses of 1.25mg / kg; 2.5mg / kg; 5mg / kg; 10mg / kg and 20mg/ kg. The treatment with MHTP (2.5mg / kg, 5mg / kg, 10mg / kg and 20mg / kg) significantly decreased (p <0.05) the migration of total cells, neutrophils and lymphocytes. Based on this experiment, the dose of 2.5mg / kg was chosen because it presented better results. Therefore, this dose was used in the other experiments. This dose also significantly decreased (p <0.05) the production of the cytokines TNF-α and IL-6 and the histological parameters such as: hemorrhage, edema, cellular infiltration and fibrosis deposition. In the 10-day period, treatment with MHTP significantly decreased (p <0.05) the migration of total cells, neutrophils, macrophages and lymphocytes with increased weight and normal return to activities in the animals. The survival rate of the MHTP treated animals was significantly (p <0.05) higher when compared to that of the LPS (sick) animals. Therefore, the results obtained in this study indicate that MHTP exerts a protective effect on acute lung injury, both in the acute phase (72h) and in the chronic phase (10 days), protecting the alveolar epithelial cells and regulating pulmonary inflammation, suggesting that MHTP is a promising therapeutic agent for the management of this disease. .